2017
DOI: 10.1017/s1463423617000019
|View full text |Cite
|
Sign up to set email alerts
|

Health team for the elderly: a feasibility study for preventive home visits

Abstract: Descriptive explorative design describing the development, utilization and feasibility of preventive home visits in two different settings. All 77-year-old persons living at home in an urban municipality and all 75 years and older in a rural municipality were invited to participate. A questionnaire including a substantial number of tests concerning; fall, nutrition, polypharmacy and cognitive impairment was used by Health Team Nurses as base for a risk assessment. Pilot studies were conducted to validate the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…Six studies reported both qualitative and quantitative data [313233343536], ten qualitative only [27293738394041424344], and three quantitative only [283045]. The numbers and characteristics of the participants involved in the included publications are given in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies reported both qualitative and quantitative data [313233343536], ten qualitative only [27293738394041424344], and three quantitative only [283045]. The numbers and characteristics of the participants involved in the included publications are given in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that joining currently disconnected professionals, extending their professional responsibilities and facilitation of knowledge sharing are untapped resources in primary care that could increase the level of work satisfaction of professionals [2740], quality of care [28324243] and improve preventive care planning [3238]. However, the habitual way in which professionals operate must be synchronized and their modes of communication systemised.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations